My one hundred adventures - Horvath, Polly (Schwartz & Wade Books, 2008)
Twelve-year-old Jane, who lives at the beach in a run-down old house with her mother, two brothers, and sister, has an eventful summer accompanying her pastor on Bible deliveries, meeting former boyfriends of her mother's, and being coerced into babysitting for a family of ill-mannered children.